English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Hello! If there is anyone here smart enough to solve this equation, I'll be very glad.

3cos2x - 5cosx = 1

helpppp!!! Pleeeaaase!!!

Thank you.

2006-12-26 11:30:00 · 9 answers · asked by Lobster 2 in Science & Mathematics Mathematics

9 answers

3cos(2x) - 5cos(x) = 1

I assume you actually mean a "2" and not a squared. With that said, remember the double angle formula:

cos(2y) = cos^2(y) - sin^2(y) = 2cos^2(y) - 1

Use this on cos(2x), and that would give us

3[2cos^2(x) - 1] - 5cos(x) = 1
6cos^2(x) - 3 - 5cos(x) = 1

Move everything to the left hand side, and sort in descending powers of cosine.

6cos^2(x) - 5cos(x) - 4 = 0

Now, we factor this like a quadratic, because that's what this is; if you don't believe me, I'll let z = cos(x). Then we have

6z^2 - 5z - 4 = 0

(3z - 4) (2z + 1) = 0

Which means

3z - 4 = 0, 2z + 1 = 0
z = {4/3, -1/2}

BUT we let z = cos(x), so what we're really solving for is

cos(x) = 4/3
cos(x) = -1/2

I'm going to assume that 0 <= x < 2pi

We can solve cos(x) = -1/2; x = {2pi/3, 4pi/3}

cos(x) = 4/3 is actually not possible. Recall that the range of cos(x) is [-1, 1], and 4/3 exceeds 1. Therefore, our only solutions are

x = {2pi/3, 4pi/3}

If we wanted the general unrestricted solutions, it would be

x =
{2pi/3 + 2k(pi) | k an integer} U
{4pi/3 + 2k(pi) | k an integer}

2006-12-26 11:43:25 · answer #1 · answered by Puggy 7 · 0 0

Use the double angle formula cos(2x) = 2cos²x - 1

3cos2x - 5cosx = 1
3(2cos²x - 1) - 5cosx - 1 = 0
6cos²x - 3 - 5cosx - 1 = 0
6cos²x - 5cosx - 4 = 0
(3cosx - 4)(2cosx + 1) = 0
cosx = 4/3, -1/2
4/3 is eliminated as impossible since cos x cannot be greater than one.

cos x = -1/2
x = {2π/3 + 2πn, 4π/3 + 2πn} where n is an integer.

2006-12-26 18:48:31 · answer #2 · answered by Northstar 7 · 0 0

use the trig identity: cos(2x) = 1 - 2 sin^2(x)

So 3*(2cos^2x-1) - 5cosx= 1
Turn this into a polynomial

6cos^2x - 5cosx - 3 - 1 = 0
6 cos^2x - 5cosx - 4 = 0
and solve for cosx using the quadratic formula!

2006-12-26 11:36:04 · answer #3 · answered by firefly 6 · 1 0

Remember the identity "cos 2x = 2(cos x)^2 -1".
The equation boils down to:

6 (cos x)^2 - 5 cos x - 4 = 0

this is a simple quadratic, hope you can take it the rest of the way!

2006-12-26 11:36:55 · answer #4 · answered by John C 4 · 1 0

Yes.

You use the double angle identity cos(2x) = 2cos(x)^2-1 then solve this quadratic for cos(x) and then use special angles. Maple answer:

> solve(3*cos(2*x)-5*cos(x)=1,x);

2/3 Pi, arccos(4/3)

Note: arccos(4/3) is not a real number, so we (usually, depending on the class) ignore this one.

2006-12-26 11:35:47 · answer #5 · answered by a_math_guy 5 · 0 0

3cos2x-5cosx=1
3(2cos^2x-1)-5cosx=1
6cos^2x-5cosx-3-1=0
6cos^2x-5cosx-4=0
6cos^2x+3cosx-8cosx-4=0
(3cosx-4)(2cosx+1)=0
cosx=4/3 or -1/2
cosx=4/3 is not admissible as cosx max=1
cosx=-1/2
cosx=cos2pi/3
x=2npi++/-2pi/3

2006-12-26 11:43:25 · answer #6 · answered by raj 7 · 0 0

i cannot. i made straight a's when i took that back in 1963. had it down cold. that is a simple equation to solve but i am sorry i tried and cannot remember. that is what happens as time goes by. i cannot remember this but a kiss is still a kiss. trig evaporates.

2006-12-26 11:40:39 · answer #7 · answered by Anonymous · 0 1

i'm not gonna answer it, you are.
Remember the Pathagarian Identity.
(sinx)^2+(cosx)^2 =1

2006-12-26 11:40:18 · answer #8 · answered by Zaza 5 · 0 0

cosx = -0.5
which means that x = 3*pi/4

2006-12-26 11:38:07 · answer #9 · answered by Andreea? 3 · 0 2

fedest.com, questions and answers